GcsR, a TyrR-Like Enhancer-Binding Protein, Regulates Expression of the Glycine Cleavage System in Pseudomonas aeruginosa PAO1 - Zaara Sarwar (American Society for Microbiology, 2016)
ABSTRACT Glycine serves as a major source of single carbon units for biochemical reactions within bacterial cells. Utilization of glycine is tightly regulated and revolves around a key group of proteins known as the glycine cleavage system (GCS). Our lab previously identified the transcriptional regulator GcsR (PA2449) as being required for catabolism of glycine in the opportunistic pathogen Pseudomonas aeruginosa PAO1. In an effort to clarify and have an overall better understanding of the role of GcsR in glycine metabolism, a combination of transcriptome sequencing and electrophoretic mobility shift assays was used to identify target genes of this transcriptional regulator. It was found that GcsR binds to an 18-bp consensus sequence (TGTAACG-N4-CGTTCCG) upstream of the gcs2 operon, consisting of the gcvH2, gcvP2, glyA2, sdaA, and gcvT2 genes. The proteins encoded by these genes, namely, the GCS (GcvH2-GcvP2-GcvT2), serine hydroxymethyltransferase (GlyA2), and serine dehydratase (SdaA), form a metabolic pathway for the conversion of glycine into pyruvate, which can enter the central metabolism. GcsR activates transcription of the gcs2 operon in response to glycine. Interestingly, GcsR belongs to a family of transcriptional regulators known as TyrR-like enhancer-binding proteins (EBPs). Until this study, TyrR-like EBPs were only known to function in regulating aromatic amino acid metabolism. GcsR is the founding member of a new class of TyrR-like EBPs that function in the regulation of glycine metabolism. Indeed, homologs of GcsR and its target genes are present in almost all sequenced genomes of the Pseudomonadales order, suggesting that this genetic regulatory mechanism is a common theme for pseudomonads. IMPORTANCE Glycine is required for various cellular functions, including cell wall synthesis, protein synthesis, and the biosynthesis of several important metabolites. Regulating levels of glycine metabolism allows P. aeruginosa to maintain the metabolic flux of glycine through several pathways, including the metabolism of glycine to produce other amino acids, entry into the trichloroacetic acid cycle, and the production of virulence factors such as hydrogen cyanide. In this study, we characterized GcsR, a transcriptional regulator that activates the expression of genes involved in P. aeruginosa PAO1 glycine metabolism. Our work reveals that GcsR is the founding member of a novel class of TyrR-like EBPs that likely regulate glycine metabolism in Pseudomonadales.